Variations in Community Prevalence and Determinants of Recreational and Utilitarian Walking in Older Age. (3rd August 2015) - Procter-Gray, Elizabeth; Leveille, Suzanne G.; Hannan, Marian T.; Cheng, Jie; Kane, Kevin; Li, Wenjun
Abstract : Background . Regular walking is critical to maintaining health in older age. We examined influences of individual and community factors on walking habits in older adults. Methods . We analyzed walking habits among participants of a prospective cohort study of 745 community-dwelling men and women, mainly aged 70 years or older. We estimated community variations in utilitarian and recreational walking, and examined whether the variations were attributable to community differences in individual and environmental factors. Results . Prevalence of recreational walking was relatively uniform while prevalence of utilitarian walking varied across the 16 communities in the study area. Both types of walking were associated with individual health and physical abilities. However, utilitarian walking was also strongly associated with several measures of neighborhood socioeconomic status and access to amenities while recreational walking was not. Conclusions . Utilitarian walking is strongly influenced by neighborhood environment, but intrinsic factors may be more important for recreational walking. Communities with the highest overall walking prevalence were those with the most utilitarian walkers. Public health promotion of regular walking should take this into account.